ARABIC-WOMAN'S RESPONSIBILITIES IN MODERN ERA (IN THE LIGHT OF QUR’AN AND SUNNAH) - Siddiqa Tahira; Azra Perveen (دی اسکالر, 2021)
Woman is an important part of human society. At every turn in human history, she has played a very important role in the development of the existence of the world along with man. Unfortunately, the woman responsible for the survival of the human race has always failed to find her rightful place in society. It is only Islam that takes strict care of women's rights and responsibilities. Through the enlightened principles of Islam, a woman's intellectual worries can be eradicated and she can be given a real place in society.In this article the struggle for women's rights in the West has been mentioned. The role of the United Nations on women's responsibilities and rights. Beijing Conference on Women. The Commission on the Status of Women. The Islamic view of women's responsibilities. Women in pre-Islamic society. Honoring women in Islam. Purposes of marriage in Islamic law. The effect of the institution of marriage in expanding the concept of responsibility. Women’s responsibilities and etiquette in the new society.  The original job that the woman is specialized in is the wife, mother and rising children. Mentioned the morals that she abide by.